Chapter Tradutor como mediador cultural. A tradução de intertextos e expressões idiomáticas em Subtilezas e crueldade da cozinha chinesa de Maria Ondina Braga - He, Meng (Studi di Traduzione Letteraria Lusofona, 2022)
Yao Jing Ming's article deals with a deep reflection on translation problems from Chinese to Portuguese languages, analysing some specifical examples of idiomatic expressions and intertextual aspects concerning a Maria Ondina Braga's chronicle which has been translated in Chinese language by He Meng in this article.